Feedback quality and divided attention: exploring commentaries on alignment in task-oriented dialogue - Ludivine Crible; Greta Gandolfi; Martin J. Pickering (Language and Cognition)
While studies have shown the importance of listener feedback in dialogue, we still know little about the factors that impact its quality. Feedback can indicate either that the addressee is aligning with the speaker (i.e. ‘positive’ feedback) or that there is some communicative trouble (i.e. ‘negative’ feedback). This study provides an in-depth account of listener feedback in task-oriented dialogue (a director–matcher game), where positive and negative feedback is produced, thus expressing both alignment and misalignment. By manipulating the listener’s cognitive load through a secondary mental task, we measure the effect of divided attention on the quantity and quality of feedback. Our quantitative analysis shows that performance and feedback quantity remain stable across cognitive load conditions, but that the timing and novelty of feedback vary: turns are produced after longer pauses when attention is divided between two speech-focused tasks, and they are more economical (i.e. include more other-repetitions) when unrelated words need to be retained in memory. These findings confirm that cognitive load impacts the quality of listener feedback. Finally, we found that positive feedback is more often generic and shorter than negative feedback and that its proportion increases over time.